1981
DOI: 10.1080/10862968109547392
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Context on the Size of the Perceptual Unit Used in Word Recognition

Abstract: Good and poor readers from the second and fourth grades read words which varied in length from 3 to 6 letters under three exposure conditions; context, miscue and no-context. Word recognition latency for the nouns in each word length category was recorded. An increase in latency relative to word length would suggest component-letter processing, while no increase would suggest holistic processing. Results indicated that under all conditions poor second grade readers used holistic processing. Poor fourth grade r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Patberg, Dewitz and Samuels, 1981;Schvaneveldt, Ackerman and Semlear, 1977;Schwantes, Boesl and Ritz, 1980; Stanovich, West and Feeman, 1981;West and Stanovich, 1978). In fact, most of these studies have shown that such context use diminishes as children grow older.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Patberg, Dewitz and Samuels, 1981;Schvaneveldt, Ackerman and Semlear, 1977;Schwantes, Boesl and Ritz, 1980; Stanovich, West and Feeman, 1981;West and Stanovich, 1978). In fact, most of these studies have shown that such context use diminishes as children grow older.…”
Section: Introductionmentioning
confidence: 95%
“…A number of studies in the past decade have shown that children, as well as adults, are able to recognize a word much more rapidly if it is presented in a related, rather than an unrelated, context (e.g. Patberg, Dewitz and Samuels, 1981; Schvaneveldt, Ackerman and Semlear, 1977;Schwantes, Boesl and Ritz, 1980; Stanovich, West and Feeman, 1981;West and Stanovich, 1978). In fact, most of these studies have shown that such context use diminishes as children grow older.…”
Section: Introductionmentioning
confidence: 99%
“…[12] consistently replicated the word length effect on processing time [2,7,19,20]. Studies also proposed that the word length effect is greater for poor readers than for skilled readers, which suggests a holistic process in skilled reading [21,22]. There are only few studies on word length effects in other orthographies.…”
Section: Introductionmentioning
confidence: 72%
“…This model assumes that reading involves a hierarchy of processes from lower order perceptual and decoding processes to higher order comprehension processes. Whereas the perceptual and decoding aspects of reading provide a bottleneck in the reading process for younger children (Curtis, 1980), more mature readers (Samuels, LaBerge, & Bremer, 1978) and better readers (Patberg, Dewitz, & Samuels, 1981) perform these lower order processes more automatically, and thus have more attention to allocate to comprehension processes. Because the perceptual and decoding processes of reading are relatively less automatic for beginning readers, and because these decoding processes are not components of television comprehension, young children who have difficulty reading do not necessarily have difficulty comprehending information presented on television.…”
Section: Resultsmentioning
confidence: 99%